Effect of superfine grinding on the physicochemical properties of bulbs of Fritillaria unibracteata Hsiao et K.C. Hsia powder - Li, Cai‐xia (Food Sci Nutr, 2019)
This work aimed to determine the influence of superfine grinding on the physicochemical properties of bulbs of Fritillaria unibracteata Hsiao et K.C. Hsia (BFU) powder. For this purpose, fine powder (FP) and two superfine powders (SPs) were obtained via superfine and conventional grinding methods. The properties of different powders were studied and compared. Compared with FP, SPs exhibited higher values in terms of the angle of repose, swelling capacity, ethanol extraction yield, total alkaloid content, and imperialine content, while lower values in terms of particle size and bulk density. Especially, the total alkaloid content of SP‐I increased by 66.7%. Proper grinding is more conducive to reduce particle size and improve alkaloid content. FTIR analysis indicates that no new functional groups produced after superfine grinding. XRD analysis suggests that grinding treatment lead to decreases in the crystallinity. Therefore, superfine grinding displays immense potential in the BFU application.